MSC-derived exosome ameliorates pulmonary fibrosis by modulating NOD 1/NLRP3-mediated epithelial-mesenchymal transition and inflammation - Wei Chen; Jie Peng; Xiangyi Tang; Shao Ouyang (Heliyon)
Background: Pulmonary fibrosis (PF) is an irreversible and usually fatal lung disease. In recent years, the therapeutic role of exosomes derived from mesenchymal stem cells (MSC-exos) in anti-fibrotic treatment has received much attention. In this study, we aimed to determine the anti-fibrotic properties and related molecular mechanisms of MSC-exos in Bleomycin(BLM)-induced PF. Methods: We used BLM-induced mice model of PF and in vitro model. MSC-exos were isolated from BMSCs cells using Exo Quick-TC kit and identified using conventional methods. Using cell counting kit-8 (CCK-8) to detect cell viability. Classic molecular biology approaches such as RT-qPCR, Western blot, immunofluorescence, and ELISA were used to examine molecular pathways. Histopathological examination was performed using HE and Masson staining. Results: MSC-exos alleviated inflammation, inhibited epithelial-mesenchymal transition (EMT), and ameliorated PF. Further studies showed that MSC-exos regulated NOD1/NF-kB signaling pathway to suppress the activation of NLRP3 inflammasomes both in vivo and in vitro. Additionally, overexpression of NLRP3 significantly reversed the anti-fibrotic effects of MSC-exos in BLM-induced lung epithelial cells. Conclusion: MSC-derived exosome ameliorates pulmonary fibrosis by modulating NOD 1/NLRP3-mediated epithelial-mesenchymal transition and inflammation.